Electrochemical Oxidation of Smooth and Nanoscale Rough Pt(111): An In Situ Surface X-ray Scattering Study. Issue 9 (7th July 2017) - Ruge, Martin; Drnec, Jakub; Rahn, Björn; Reikowski, Finn; Harrington, David A.; Carlà, Francesco; Felici, Roberto; Stettner, Jochim; Magnussen, Olaf M.
Abstract : The potential dependent surface structure of Pt(111) electrodes in electrochemical environment was studied by in situ crystal truncation rod measurements and in operando grazing incidence small angle X-ray scattering. Determination of the interface structure in the oxidation region reveal a continuous increase of the coverage of place exchanged atoms toward more positive potentials. The resulting oxide consists of an oxygen rich outer and a Pt-rich inner atomic layer. With increasing potential the oxide approaches a more uniform stoichometry. While place exchange on atomically smooth terraces only occurs above 1.05 V, structural changes of 3D Pt islands, grown by repetitive oxidation/reduction cycles, already commence at 0.8 V, which is assigned to oxidation at Pt steps. Evolution of the 3D island distribution occurs in all stages of the cycles: Whereas Pt oxidation leads to narrowing of the lateral size distribution, vertical island growth occurs during the subsequent reduction.